Sonata for violin and piano in E minor, op 46, 2nd movement - Esposito, Michele; Cooper, Mia; Coburn, Lance (Champs Hill Records, 2013)
Michele Esposito spent almost his whole professional life in Ireland, and he was a respected and hugely influential figure throughout that time - indeed, a very lynch-pin of Irish musical life. Though his own compositions have suffered a period of eclipse, they are undergoing a gradual revival, as the present recording demonstrates.
Esposito: Violin and cello sonatas
Mia Cooper (Violin); Lance Coburn (Piano)
Keywords: Music; Esposito, Michele, 1855-1929; Sonatas (Violin and piano); Violin and piano music